Exploring Social Networks to Understand the Diffusion of Networked Learning in a Campus-Based University - Hanson, Janet (Proceedings of the International Conference on Networked Learning, 2004)
This paper seeks to explain the nature of the diffusion of networked learning within a campus-based university. It explores the concerns held by university lecturers about greater use of networked learning and identifies the key individuals who influence their attitudes. These are mainly close colleagues within their academic department. It then proposes directions for further investigation into strategies that might encourage and sustain further innovation within the university. The research is being undertaken within an action inquiry approach where an important consideration for the insider researcher is the influence of her position on the research process.